Evolution of a pulse of noninteracting quasiparticles with dispersion and initial angular width - Adamenko, I.N.; Nemchenko, K.E.; Slipko, V.A.; Wyatt, A.F.G. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
The evolution of a pulse of noninteracting quasiparticles, caused by their different velocities and angular distribution of momenta, is studied theoretically. Equations are found that describe the shape of the pulse surface at any time. The time of the beginning, end and duration of the density of the quasiparticle energy flux is determined at a general spatial point. The quasiparticle energy density is considered at all times and positions, and it is shown that the region of high energy density, in the middle of the pulse, is equal to the initial energy density under certain conditions. These theoretical results are discussed in relation to experimental data on the evolution of a pulse of noninteracting phonons in superfluid helium.